2015
DOI: 10.1007/s00464-015-4374-8
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal symptoms, weight loss and patient satisfaction 5 years after gastric bypass: a study of three techniques for the gastrojejunal anastomosis

Abstract: Our data suggest that the technique for the construction of the GJ in RYGB affects gastrointestinal symptoms 5 years postoperatively. The difference is moderate but indicates that a narrow GJ results in increased frequency of vomiting and need for endoscopic interventions without improving the weight result.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 28 publications
(32 reference statements)
2
12
0
Order By: Relevance
“…Many series have shown that the use of a 21-mm circular stapler is associated with higher rates of stricture. Our 17% stricture rate with the 21-mm circular stapler is consistent with previous reports revealing high stricture rates in the range of 12.5 to 27% [ 3 , 14 , 15 ]. Sima et al reported a greater incidence of vomiting and need for endoscopic dilation over a 5-year follow-up period in those patients for whom the C21 technique was used for GJA [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Many series have shown that the use of a 21-mm circular stapler is associated with higher rates of stricture. Our 17% stricture rate with the 21-mm circular stapler is consistent with previous reports revealing high stricture rates in the range of 12.5 to 27% [ 3 , 14 , 15 ]. Sima et al reported a greater incidence of vomiting and need for endoscopic dilation over a 5-year follow-up period in those patients for whom the C21 technique was used for GJA [ 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…Our 17% stricture rate with the 21-mm circular stapler is consistent with previous reports revealing high stricture rates in the range of 12.5 to 27% [ 3 , 14 , 15 ]. Sima et al reported a greater incidence of vomiting and need for endoscopic dilation over a 5-year follow-up period in those patients for whom the C21 technique was used for GJA [ 14 ]. However, some authors have demonstrated low rates of GJ stricture with the 21-mm staplers (0.8–5.9%) [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 92%
“…As a result, RYGB markedly accelerates gastric emptying of liquids and solids (although emptying of small, solid meals with volumes not exceeding the pouch volume may be slower) (213,244,339,518,536,802,808). This, in turn, often leads to bloating, nausea, and dumping in RYGB patients (307,377,545,695,745). Glucose solutions, as used in glucose-tolerance tests, may empty almost immediately in RYGB patients, leading to the appearance of ϳ300 kcal in the jejunum within 1-2 min (544).…”
Section: G Rygbmentioning
confidence: 99%
“…In one series, 87.4% of the patients felt better or much better although 67.6% had been in contact with health care due to symptoms, most commonly abdominal pain (11). In another study, 31% of the patients reported abdominal pain, but 88% were satisfied or very satisfied with the procedure, and 92% would recommend RYGB to an acquaintance (6). These findings should be interpreted with care, but well-being and the acceptance of symptoms may depend in part on improvement or resolution of other symptoms.…”
Section: Discussionmentioning
confidence: 99%